An assessment of adherence to basic ecological principles by payments for ecosystem service projects. Issue 4 (22nd February 2016) - Prager, C.M.; Varga, A.; Olmsted, P.; Ingram, J.C.; Cattau, M.; Freund, C.; Wynn‐Grant, R.; Naeem, S.
Abstract: Programs and projects employing payments for ecosystem service (PES) interventions achieve their objectives by linking buyers and sellers of ecosystem services. Although PES projects are popular conservation and development interventions, little is known about their adherence to basic ecological principles. We conducted a quantitative assessment of the degree to which a global set of PES projects adhered to four ecological principles that are basic scientific considerations for any project focused on ecosystem management: collection of baseline data, identification of threats to an ecosystem service, monitoring, and attention to ecosystem dynamics or the formation of an adaptive management plan. We evaluated 118 PES projects in three markets—biodiversity, carbon, and water—compiled using websites of major conservation organizations; ecology, economic, and climate‐change databases; and three scholarly databases (ISI Web of Knowledge, Web of Science, and Google Scholar). To assess adherence to ecological principles, we constructed two scientific indices (one additive [ASI] and one multiplicative [MSI]) based on our four ecological criteria and analyzed index scores by relevant project characteristics (e.g., sector, buyer, seller). Carbon‐sector projects had higher ASI values ( P < 0.05) than water‐sector projects and marginally higher ASI scores ( P < 0.1) than biodiversity‐sector projects, demonstrating their greater adherence to ecological principles. Projects financed by public–private partnerships had significantly higher ASI values than projects financed by governments ( P < 0.05) and marginally higher ASI values than those funded by private entities ( P < 0.1). We did not detect differences in adherence to ecological principles based on the inclusion of cobenefits, the spatial extent of a project, or the size of a project's budget. These findings suggest, at this critical phase in the rapid growth of PES projects, that fundamental ecological principles should be considered more carefully in PES project design and implementation in an effort to ensure PES project viability and sustainability.